Lysimachia savranii (Primulaceae), a new species from the eastern Taurus in Turkey - Başköse İsa; Keski̇n Ali̇; Gurbanov, Kamal (Phytotaxa, 2016)
The genus Lysimachia Linnaeus (1753: 146) comprises about 180 species, distributed in temperate and subtropical parts of the northern hemisphere, as well as in some tropical mountain regions (Ray 1956). The majority of species grows in China, i.e. Yunnan, Southern Sichuan, Western Guizhou and Guangxi regions (Hu & Kelso 1996), which is also considered the centre of origin of this genus (Chen & Hu 1979). A limited number of species can be found in North America (20; Cholewa 2009), in Europe (13; Ferguson 1972), in Russia (11; Fedorov 1967), with 7 species occurring in Turkey (Coşkunçelebi 2012).